New Light on NO Bonding in Fe(III) Heme Proteins from Resonance Raman Spectroscopy and DFT Modeling - Soldatova, Alexandra V. (2010)
Visible and ultraviolet resonance Raman (RR) spectra are reported for Fe(III)(NO) adducts of myoglobin variants with altered polarity in the distal heme pockets. The stretching frequencies of the Fe(III)–NO and N–O bonds, ν(FeN) and ν(NO), are negatively correlated, consistent with backbonding. However, the correlation shifts to lower ν(NO) for variants lacking a distal histidine. DFT modeling reproduces the shifted correlations, and shows the shift to be associated with the loss of a lone-pair donor interaction from the distal histidine that selectively strengthens the N–O bond. However, when the model contains strongly electron-withdrawing substituents at the heme β-positions, ν(FeN) and ν(NO) become positively correlated. This effect results from Fe(III)–N–O bending, which is induced by lone pair donation to the N(NO) atom. Other mechanisms for bending are discussed, which likewise lead to a positive ν(FeN)/ν(NO) correlation, including thiolate ligation in heme proteins and electron-donating meso-substituents in heme models. The ν(FeN)/ν(NO) data for the Fe(III) complexes are reporters of heme pocket polarity and the accessibility of lone pair, Lewis base donors. Implications for biologically important processes, including NO binding, reductive nitrosylation and NO reduction, are discussed.